The 'Go's and the 'No-Go's of response-inhibition training to food: lessons learned from trials. (December 2022) - Lawrence, Natalia S; Porter, Lucy; Staiger, Petra K
Abstract : High food-reward sensitivity and low inhibitory control are modifiable targets for overeating interventions. Our review of 16 food-related response-inhibition training (RIT) trials identified key elements linked to effectiveness, including recruiting from at-risk populations (i.e. those with overweight or heightened snacking behaviour), and designing intervention tasks to support bottom-up, associative (food-inhibition) learning. The optimal comparison condition depends on the research question, but the most consistent training effects have been seen relative to generalised (non-food) RIT. Trial outcomes should prioritise objective and validated measures (e.g. weight loss and explicit food devaluation). Future trials should consider unanswered questions such as training schedules and timing, and whether training people to 'go' to healthy foods can increase their appeal. Highlights: Review of 16 recent real-world trials of food-related response-inhibition training. Identifies key elements linked to positive training effects. Encourages the recruitment of at-risk populations. Recommends and describes interventions that train associative inhibition. Recommends objective (weight) and validated (food devaluation) trial outcomes.